2018
DOI: 10.22146/agritech.31850
|View full text |Cite
|
Sign up to set email alerts
|

Efek Antioksidatif dan Akseptabilitas Bakso Daging Ayam Ras dengan Penambahan Gel Lidah Buaya

Abstract: Currently, the consumption of broiler-chicken meat increases up to 3.7510 kg/cap/year. This condition is due to the increasing of population growth and food businesses which use chicken meat. On the other hand, the chicken meat contains of high fat, thus easily oxidized and resulted in free radicals and off- flavor. Chicken meat is widely used as meatball that is processed through the stage of meat-milling and boiling which triggers fat oxidation. Therefore, an antioxidant is needed to inhibit oxidation. Aloev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…Untuk menyeimbangkan tekstur dimsum siomay agar tidak terlalu kenyal dan keras, serta memberikan rasa juicy, maka perlu penambahan es batu. Penambahan es batu dapat menurunkan suhu pada adonan, sehingga menghindari proses gelatinasasi terbentuk sempurna (Wariyah & Riyanto, 2018). Penggunaan tepung tapioka dan penambahan es batu merupakan variabel kontrol, sehingga menyebabkan tidak ada perbedaan yang signifikan pada setiap perlakuan.…”
Section: Hasil Dan Pembahasanunclassified
“…Untuk menyeimbangkan tekstur dimsum siomay agar tidak terlalu kenyal dan keras, serta memberikan rasa juicy, maka perlu penambahan es batu. Penambahan es batu dapat menurunkan suhu pada adonan, sehingga menghindari proses gelatinasasi terbentuk sempurna (Wariyah & Riyanto, 2018). Penggunaan tepung tapioka dan penambahan es batu merupakan variabel kontrol, sehingga menyebabkan tidak ada perbedaan yang signifikan pada setiap perlakuan.…”
Section: Hasil Dan Pembahasanunclassified
“…Skala hedonik bernilai 1-5, dimana nilai 1 (satu) berarti sangat tidak suka, hingga nilai 5 (lima) yang berarti sangat suka. Warna bakso ditentukan oleh daging ayam ras yang digunakan (Wariyah & Riyanto, 2018). Bakso ayam pada pengamatan ini berwarna putih karena terbuat dari ayam broiler yang termasuk daging putih dan lebih disukai oleh konsumen (Montolalu et al, 2013).…”
Section: Uji Organoleptik 1 Warnaunclassified
“…Substitution cassava starch with rice bran was able to increase antioxidant activity and total phenolic contents of meatballs. Since meatball was added by fried garlic and fried red onion which contains antioxidant (Rohmawati et al, 2016), meatball without rice bran has also antioxidant activity 16,75% and total phenolic content 37.82 mg/100 g. Wariyah and Riyanto (2018) reported that substitution ice with Aloe vera gel to chicken meatball increased antioxidant activity of meatball, but it is only from 5.51 (control) to 12.89% (60% substitution). When substituted with rice bran (50% to 100% from cassava starch), antioxidant activity was increased significantly (P<0.05) from 19.71 to 55.21% and total phenolic content from 84.06 to 100.76 mg/100 g. Antioxidant activity and total phenolic content increased significantly (p≤0.05) as the percentage of substitution with rice bran were increased.…”
Section: Effect Of Substitution With Rice Bran In Meatballs To Antioxmentioning
confidence: 99%